2009
DOI: 10.1016/j.bbr.2009.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Chronic prenatal caffeine exposure impairs novel object recognition and radial arm maze behaviors in adult rats

Abstract: In this report, we demonstrate that chronic prenatal exposure to a moderate dose of caffeine disrupts novel object recognition and radial arm maze behaviors in adult male and female rats. Pregnant dams were administered either tap water or 75 mg/L caffeinated tap water throughout gestation. Oral self-administration in the drinking water led to an approximate maternal intake of 10 mg/kg/day, equivalent to 2–3 cups of coffee/day in humans based on a metabolic body weight conversion. In adulthood, the offspring u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 49 publications
1
23
1
11
Order By: Relevance
“…No significant difference was observed in the body mass of the pups in the birthday. The consumption of caffeine by mothers during gestation has been associated with a low body mass of the pups at birth, or caused no alteration in the body mass of pups 15 . In addition, present results reinforce the hypothesis that caffeine has anorectic effects by promoting satiety and reducing body mass gain in the offspring 16 , since the caffeine-treated group presented a reduction in the food consumption and the body mass gain.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was observed in the body mass of the pups in the birthday. The consumption of caffeine by mothers during gestation has been associated with a low body mass of the pups at birth, or caused no alteration in the body mass of pups 15 . In addition, present results reinforce the hypothesis that caffeine has anorectic effects by promoting satiety and reducing body mass gain in the offspring 16 , since the caffeine-treated group presented a reduction in the food consumption and the body mass gain.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational caffeine also downregulates central adenosine receptors (Leon et al, 2005;Lorenzo et al, 2010), reduces NMDA antagonist-induced locomotor activity (da Silva et al, 2005), and affects respiratory control (Bodineau et al, 2003;Saadani-Makki et al, 2004). Cognitive and motor deficits have also been reported in adult rodents exposed in caffeine during gestation and/or early postnatal life (Bjorklund et al, 2008;Soellner et al, 2009), although some impairments may be paradigm specific (Soellner et al, 2009).…”
Section: Caffeinementioning
confidence: 99%
“…Since then, a number of studies have confirmed the negative effect of high doses of caffeine ingested during pregnancy both for the mother and the developing foetus [2,3,7,15,16,18,22,25,27,30,31].…”
Section: Introductionmentioning
confidence: 99%